ANALISIS EFEKTIVITAS PENERAPAN SISTEM INFORMASI AKUNTANSI APLIKASI E-BENGKEL TERINTEGRASI PADA BENGKEL WIRTA MOTOR - Luh Putu Armalia Ekayanti; I Gede Putu Banu Astawa (Universitas Pendidikan Ganesha, 2022)
This study aims to examine the effectiveness of the application of the Integrated E-Bengkel Application Accounting Information System at the Wirta Motor Workshop. This study was designed using a descriptive qualitative method. Data were collected through a process of observation and interviews with 3 sources. The validity of the data is supported by the source triangulation technique. The results of the study show that: (1) The Integrated E-Bengkel Application Accounting Information System has been running effectively, seen from several components or features that are directly connected, and has worked well with the business processes at the Wirta Motor Workshop. (2) The results of the success achieved include the quality of the integrated system, the suitability of electronic and physical documents, the quality of the information produced is relevant and accurate, the service quality of application providers with data security is guaranteed, ease of use, the readiness of adequate resources and satisfaction user. (3) Constraints from the implementation, namely the information generated is sometimes not on time due to the website experiencing downtime.